Assessment of Genetic Variation among Hatchery Populations of the Indian Major Carp, Catla, Labeo catla (Hamilton, 1822) Using RAPD Markers - Panathila, Sheethal; Rajanna, K. B.; Satyaveer; Nayak, Harsha; C, Sruthisree (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Genetic variation is regarded as a key factor for adaptation to the changing environment, therefore, in this study, genetic variations of Labeo catla were analysed using Randomly Amplified Polymorphic DNA (RAPD). The Catla (Labeo catla) seeds were procured from three distinct geographical locations viz., West Bengal, Andhra Pradesh, and Karnataka. The growth performance of Catla were conducted for period of 120 days under different environmental and management conditions. Growth trials resulted better performance of Andhra Pradesh stock followed by West Bengal and Karnataka. For assessment of genetic variation 140 decamer primers were screened, out of which, 6 primers (OPA02, OPA04, OPA07, OPA10, OPB07 and OPB10) that yielded consistent and significant polymorphism were selected for RAPD analysis which indicated West Bengal stock being more polymorphic (60.55%) in comparison with Karnataka and Andhra Pradesh stocks. Higher Shannon's diversity (0.2957) and Nei's heterozygosity (0.2017) was observed in the West Bengal stock. In terms of genetic identity and genetic distance, Karnataka and Andhra Pradesh stocks showed a genetic distance of 0.7101 and a minimum Genetic identity of 0.4916, while West Bengal and Karnataka stocks indicated a maximum genetic identity of 0.6290 and a minimum genetic distance of 0.4637. The study also showed Karnataka stock being closely related to West Bengal stock when compared to Andhra Pradesh stock. The r2 values of 0.00238 showed a positive correlation between the percentage of polymorphism and mean body weight attained by different stocks of Labeo catla.